Stryphnodendron adstringens and purified tannin on Pythium insidiosum: In vitro and in vivo studies - Trolezi, Rodrigo [UNESP]; Azanha, Juliana Maziero [UNESP]; Paschoal, Natália Rodrigues [UNESP]; Chechi, Jéssica Luana [UNESP]; Dias Silva, Marcelo José [UNESP]; Fabris, Viciany Eric [UNESP]; Vilegas, Wagner [UNESP]; Kaneno, Ramon [UNESP]; Fernandes Junior, Ary [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP] (Springer Nature, 2017)
Background: Pythium insidiosum is the etiological agent of pythiosis, an emerging life-threatening infectious disease in tropical and subtropical regions. The pathogen is a fungus-like organism resistant to antifungal therapy, for this reason, most cases need extensive surgical debridments as treatment, but depending on the size and anatomical region of the lesion, such approach is unfeasible. We investigate the fungicidal effect and toxicity of crude bark extract of Stryphnodendron adstringens and commercially available tannin on Pythium insidiosum both in vitro and in vivo. Methods: Standardized fragments of mycelia of fifteen isolates of P. insidiosum were tested with different concentrations of bark extract (10 to 30% v/v) and tannin (0.5, 1.0 and 1.5 mg/mL). For in vivo study, fifteen rabbits were experimentally infected with zoospores of P. insidiosum and treated by oral and intralesional applications of bark extract and tannin. Acute toxicity tests with both substances were also performed in rats. Results: In vitro studies showed fungicidal effect for both substances at different concentrations and the SEM showed alteration on the cell wall surface of the pathogen. All infected rabbits developed a firm nodular mass that reached around 90 mm2 ninety days after inoculation, but neither the intralesional inoculation of tannin, nor the oral administration of crude extract and tannin were able to promote remission of the lesions. Conclusions: Lesions developed by rabbits presented an encapsulated abscess being quite different of naturally acquired pythiosis, which is characterized by ulcerated lesions. Since no toxicity was observed in rats or rabbits inoculated with these products, while in vitro experiments showed direct antifungal effect, therapeutic activity of S. adstringens and tannin should be clinically tested as an alternative for healing wounds in naturally acquired pythiosis.
Keywords: Oomycete; Pythiosis; Pythium insidiosum; Susceptibility tests